THE ADDITION OF BRAIN GYM ON PROPRIOCEPTIVE EXERCISE IS BETTER THAN PROPRIOCEPTIVE EXERCISE TO IMPROVING STATIC BALANCE IN CHILDREN 8-9 YEARS OLD. - Martini, Ni Made Dwi Dayanti; Winaya, I Made Niko; Primayanti, I Dewa Ayu Inten Dwi (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p11, 2018)
ABSTRACT The balance is a major component in maintaining the posture of the human body that used to erect and maintaining the position of the body. In children 8-9 years old, the static balance is extremely influenced by their physical activities. This research is an Experimental Research with study design Randomized  Pre and Post Test Control Group Design and the sampling technique is simple random sampling. Samples are 24 students at SDN 4 Ketewel that divided into two groups. The average difference between the increase on the first treatment group is 25.83 ± 10.659 and the average difference between the increase on the second treatment group is 12.00 ± 6.353, with p value = 0.001. Concluded that the addition of brain gym on proprioceptive exercise is better than proprioceptive exercise to improving static balance in children 8-9 years old. Keywords: Brain Gym, Proprioceptive Exercise, Static Balance, Standing Stork Test